2001
DOI: 10.1054/bjoc.2001.1722
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors and lung cancer risk in Japanese: with special reference to fish consumption and adenocarcinomas

Abstract: To investigate risk modification for lung cancer with diet in Japanese, we conducted a hospital-based case–control study and evaluated variation in influence with the histological type. We recruited 367 male and 240 female cases with adenocarcinomas, and 381 male and 57 female cases with squamous cell and small cell carcinomas. Controls comprised 2964 male and 1189 female cancer-free outpatients matched for sex and age with the cases. Odds ratios (ORs) and their 95% confidence intervals (CIs) for lung cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 37 publications
1
70
1
3
Order By: Relevance
“…In addition, we and others have previously reported that soy product consumption is associated with a decreased risk of all NSCLCs. (26)(27)(28)(29) These findings may provide insights into both the genesis and differentiation of NSCLCs. Soybean isoflavones are heterocyclic phenols closely related in structure to estrogen and their very weak estrogenic activity despite higher affinity for estrogen receptors than estrogens themselves endows them with antiestrogenic effects.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we and others have previously reported that soy product consumption is associated with a decreased risk of all NSCLCs. (26)(27)(28)(29) These findings may provide insights into both the genesis and differentiation of NSCLCs. Soybean isoflavones are heterocyclic phenols closely related in structure to estrogen and their very weak estrogenic activity despite higher affinity for estrogen receptors than estrogens themselves endows them with antiestrogenic effects.…”
Section: Discussionmentioning
confidence: 90%
“…[12][13][14][15][16][17][18][19][20][21][27][28][29][30][31][32][33][34][35][36] The magnitude of relative risk in Japan ranged from 3.7-5.1 for all histologic types combined, either from cohort or case-control studies. When divided by histologic type, findings from a case-control study indicated that odds ratios ranged from 4.3-21.4 for squamous cell and small cell carcinoma and from 1.5-3.7 for adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…12 European countries also reported that the risk of lung adenocarcinoma was much higher for current smokers than non-smokers, i.e., 8.0 times higher for men and 4.1 times for women in a case-control study recently conducted in 6 countries (1988 -1994), 13 while in a case-control study in 5 countries conducted previously (1976 -1980) corresponding estimates were 3.5 and 1.8 for men and women, respectively. 14 In Asian countries, however, the relative risk of lung adenocarcinoma associated with cigarette smoking have been reported to be less than 2-3, much lower than those reported in the US or Europe, [15][16][17][18][19][20][21] and there have been few recent updated reports.…”
mentioning
confidence: 97%
“…Additional case-control or cohort studies in Norway, Hong Kong, Australia, the United Kingdom, and Japan (the latter focused solely on adenocarcinomas) likewise have found that consumption of fish or fish liver oil correlates inversely with lung cancer risk or mortality [14][15][16][17]. A trend (p = 0.08) toward protection with fresh fish consumption was also reported in a study from New Caledonia [18].…”
Section: Fish Consumption May Protect Smokers From Lung Cancermentioning
confidence: 71%